Variations in atmospheric concentrations and isotopic compositions of gaseous and particulate boron in Shizuoka City, Japan. (January 2017) - Sakata, Masahiro; Phan, Hang Giang; Mitsunobu, Satoshi
Abstract: To clarify the partitioning and isotopic fractionation of boron (B) into the gas and particle phases in the atmosphere, the concentrations and isotopic compositions of gaseous and particulate B were measured concurrently for more than one year at a site in Shizuoka City, Japan. This area has few anthropogenic sources of B, such as coal combustion facilities. Gaseous B concentration showed clearly a seasonal variation, increasing during summer and decreasing during winter. Conversely, particulate B concentration tended to decrease during the warm season and increase during winter. The increase in gaseous B concentration during summer is attributable to the enhanced emissions of B from sea-salt degassing owing to higher temperatures and the predominance of winds from the Pacific Ocean. Moreover, the decrease in gaseous B concentration and the increase in particulate B concentration during winter is probably due to the enhanced condensation of gaseous B on atmospheric particles. The δ 11 B values of gaseous and particulate B varied largely, and did not indicate a distinctive seasonal variation. A positive correlation was observed between the δ 11 B values of gaseous and particulate B (R 2 = 0.518, P < 0.001). Moreover, the δ 11 B values of particulate B were approximately 0–20‰ lower than those of gaseous B. There is an isotopic fractionation ( Δ B ( OH ) 4 − − B ( OH ) 3 ) of about −20‰ between B(OH)3 and B ( OH ) 4 − species in solution (Kakihana et al., 1977). This tends to support the hypotheses that gaseous B is transformed to particulate B through the reaction of condensed B(OH)3 with chemical constituents on particles to precipitate borates, and that the condensed B(OH)3 remaining on particles is unstable and evaporates. Highlights: The concentrations and δ 11 B of gaseous and particulate B were measured concurrently. There was a strong temperature dependence on the phase partitioning of B. A positive correlation was observed between the δ 11 B of gaseous and particulate B. Particulate B is enriched in 10 B relative to gaseous B due to isotopic fractionation. Gaseous B may be transformed to particulate B through the precipitation of borates.